PENTINGNYA EDUKASI KEUANGAN KELUARGA - Widyartono, Agustinus; Kewal, Suramaya Suci; Putranto, Yohanes Andri; Mendari, Anastasia Sri; Heriyanto, Heriyanto (Jurnal Abdimas Musi Charitas, 2021)
Community Service Activities are carried out by the team and partners in an online form using zoom. The zoom link is prepared by the partner. Providing material on "Financial Planning Training: The Importance of Family Financial Education" is important considering that one of the problems in the family is financial problems. The partner of this service, namely the Family Commission of the Dean 1 of the Archdiocese of Palembang, entrusted this material to a team of lecturers from the Faculty of Business and Accounting, Musi Charitas Catholic University, Palembang. This training was attended by 56 participants from various parishes, but 45 participants filled out the questionnaire distributed by the team. Financial Planning Training: The Importance of Family Financial Education has been going well, and partners also expressed their gratitude for holding this activity, and hoped that similar activities would be held again. The targets (output targets) in this activity were also quite achieved, with an increase in correct answers after participants attended the training.